Acetylation and Deacetylation of DNA Repair Proteins in Cancers - Li, Shiqin; Shi, Bingbing; Liu, Xinli; An, Han-Xiang (Frontiers in Oncology, 2020)
Hundreds of DNA repair proteins in the DDR coordinate together to remove the offending damage ensuring the integrity and stability of the genome. In a broad sense, DDR and repair systems are an extensive network mainly encompassing cell cycle checkpoint activation, cell-cycle arrest, chromatin remodeling, and regulation of new DNA chain synthesis. Acetylation on DNA repair proteins is a dynamic epigenetic modification charged by HATs and HDACs that dramatically affects the protein functions through multiple mechanisms, such as by regulating DNA binding ability, protein instability and activity, PTM crosstalk, and protein-protein interaction. It is now increasingly becoming clear that aberrant acetylation/deacetylation of repair proteins may attribute to the dysfunction of DNA repair ability, driving the pathogenesis and progress, as well as affecting the chemo-sensitivity of cancer cells. In the present scenario, targeting epigenetic therapy is being considered as a promising method at par with the conventional cancer therapeutic strategies. This article provides an overview of the recent progress in the functions and mechanisms of acetylation on repair proteins involved in five major repair pathways, which warrants the possibility of regulating acetylation on repair proteins as a therapeutic target in cancers.